'We Don't Have This Is Mine and This Is His': Managing Money and The Character of Conjugality in Kenya. Issue 5 (4th May 2017) - Johnson, Susan
Abstract: In the context of calls for more nuanced understanding of marriage as a dynamic institution, this paper addresses a gap in the literature on intra-household financial management. It examines financial management systems and levels of cooperation among 51 married couples in Kenya. It first presents a typology of intra-household financial management arrangements and then examines how this relates to the nature of cooperation between couples. It reveals a wide spectrum of cooperation which highlights the neglected case of strong cooperation, which is found to be more frequent among younger couples. There is some evidence that this is the result of changing ideologies towards companionate marriage but there is also evidence of life-cycle influences which result in declining cooperation over time.